2009
DOI: 10.1063/1.3065669
|View full text |Cite
|
Sign up to set email alerts
|

Double excitations in finite systems

Abstract: Time-dependent density-functional theory (TDDFT) is widely used in the study of linear response properties of finite systems. However, there are difficulties in properly describing excited states, which have double- and higher-excitation characters, which are particularly important in molecules with an open-shell ground state. These states would be described if the exact TDDFT kernel were used; however, within the adiabatic approximation to the exchange-correlation (xc) kernel, the calculated excitation energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 48 publications
1
134
0
Order By: Relevance
“…16−21 Over the past 20 years, the TDDFT approach has become the workhorse in DFT-based studies of excited states, and its strengths and weaknesses are well documented. 22 −37 On the other hand, progress beyond the adiabatic approximation has been slow, although work in this direction is ongoing. 38−40 TDDFT has the distinct advantage over ΔSCF that it can deal with states that are multideterminantal.…”
Section: Introductionmentioning
confidence: 98%
“…16−21 Over the past 20 years, the TDDFT approach has become the workhorse in DFT-based studies of excited states, and its strengths and weaknesses are well documented. 22 −37 On the other hand, progress beyond the adiabatic approximation has been slow, although work in this direction is ongoing. 38−40 TDDFT has the distinct advantage over ΔSCF that it can deal with states that are multideterminantal.…”
Section: Introductionmentioning
confidence: 98%
“…Recent work has demonstrated that higher excitations only arise in the above theories with the retention of a frequency dependent interaction kernel. 46,47 Specifically, one solves the eigenvalue-like equation, H(ω)c = ωc, with…”
Section: Aside Regarding Wavefunction Free Methodsmentioning
confidence: 99%
“…62,66,70,78,80 Frequency-dependent exchange-correlation kernels have been proposed recently and tested on model systems. 81,82 …”
Section: B Restricted Excitation Window Tddftmentioning
confidence: 99%